Differences in Egyptian Students’ Attitudes to Academic Dishonesty and Related Behaviors: The Case of Business Students - Metwally, Dina (Journal of Education and Vocational Research, 2014)
Academic cheating is one type of unethical academic behaviors or academic dishonesty. The level of cheating among undergraduate students has tremendously increased. Academic cheating is crucial as it affects the credibility and predictive accuracy in university admission criteria. Despite the concern with academic dishonesty (cheating), most research has been conducted in Western context. Western research has been useful in providing in-depth understanding of causes of academic cheating however; it is uncertain whether the same research findings are applicable to Arab/Middle Eastern countries. This study focuses on academic cheating among Egyptian undergraduate students. The aim is to explore differences in students’ attitudes and reported behaviors to cheating across academic years. Research findings report no significant difference among business students with regard to behaviors and attitudes to academic dishonesty. Except for few statements, students have similar responses to the used scenarios. Findings of this study have important implications to the faculty and its staff. More attention should be given to the communication of right academic behaviors to students, students’ evaluation and assessment, invigilation system, punishment of wrong behaviors, and evaluation of academics.